2013
DOI: 10.1088/0031-9155/58/13/4659
|View full text |Cite
|
Sign up to set email alerts
|

Tumor tracking based on correlation models in scanned ion beam therapy: an experimental study

Abstract: Accurate dose delivery to extra-cranial lesions requires tumor motion compensation. An effective compensation can be achieved by real-time tracking of the target position, either measured in fluoroscopy or estimated through correlation models as a function of external surrogate motion. In this work, we integrated two internal/external correlation models (a state space model and an artificial neural network-based model) into a custom infra-red optical tracking system (OTS). Dedicated experiments were designed a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
36
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(37 citation statements)
references
References 42 publications
1
36
0
Order By: Relevance
“…Geometric results showed that the correlation models transversal (2D) targeting error was always lower than 1.3 mm (root mean square). A significant decrease of the dosimetric error with respect to the uncompensated irradiation was achieved in four out of six experiments, demonstrating that phase shifts are the most critical irregularity for external/internal correlation models [48].…”
Section: Respiratory Gating and Repaintingmentioning
confidence: 75%
See 1 more Smart Citation
“…Geometric results showed that the correlation models transversal (2D) targeting error was always lower than 1.3 mm (root mean square). A significant decrease of the dosimetric error with respect to the uncompensated irradiation was achieved in four out of six experiments, demonstrating that phase shifts are the most critical irregularity for external/internal correlation models [48].…”
Section: Respiratory Gating and Repaintingmentioning
confidence: 75%
“…Real-time tumour tracking based on external surrogates has been tested as future clinical implementation, allowing full motion compensation at any respiratory phase [46]. Experimental data acquired during the tumour tracking sessions performed at GSI over the years 2011e2012 have been assessed in order to support strategies for tumour tracking in particle therapy [47,48]. Two internaleexternal correlation models for internal target position estimation from external surrogates have been implemented and tested: a state space model (SSM) and an artificial neural network (ANN).…”
Section: Respiratory Gating and Repaintingmentioning
confidence: 99%
“…thoracoabdominal surface) movement registered by noninvasive optical devices. 28,29,40 Another solution is the prediction of the motion pattern based on respiratory-correlated CT [four-dimensional CT (4DCT)]. It is worth looking at the individual motion-monitoring techniques in the context of their usefulness in hadron therapy.…”
Section: Motion Monitoringmentioning
confidence: 99%
“…However it has been designed to allow enough flexibility to implement tracking, gating or repainting techniques to treat tumors in moving organs [26,27,28]. 555…”
Section: Discussion 535mentioning
confidence: 99%
“…The current system is well optimized for the treatment of static tumors. However, it has been designed to allow enough flexibility to implement tracking, 32 gating, or repainting techniques [33][34][35] to treat tumors in moving organs. 36 The ability of the DDS to accomplish a safe and accurate treatment was validated during the commissioning phase, some examples being reported in this paper.…”
Section: Discussionmentioning
confidence: 99%